The Role of Istisna'a Contracts in Achieving Economic Development An Applied Study on Commercial Banks in the City of Benghazi (Comprehensive Journal of Science, 2025)
The study aims to identify the role of Istisna'a contracts in achieving economic development within commercial banks. To achieve its objectives, the study relied on the analytical descriptive methodology to survey the opinions of the study sample, represented by employees, totaling (52) employees. After distributing the questionnaire, (48) valid forms were retrieved for analysis. These were processed using SPSS, The general results of the study revealed that Istisna'a contracts play a role in achieving economic development in commercial banks. Finally, the study reached a set of recommendations and proposed solutions, the most important of which are: The study recommends focusing on Istisna'a contracts due to their contribution in attracting the necessary financial resources to fund various projects, The study also recommended allocating sufficient financial amounts for the training and development of employees working in the field of Istisna'a contracts, The study recommended working to enhance the role of Istisna'a contracts and their participation in financing public projects, thereby assisting governments in bridging their budget deficits.
Keywords: Istisna'a contracts, Economic development, Commercial banks